Mystic, geometer, and intuitionist the life of L E J Brouwer - Dalen Dirk van (Oxford Clarendon Press, 1999)
This book, the second in a two volume set, provides a sophisticated analysis of this crucial era of mathematical research, but also gives an important insight into the wider life of one of the most fascinating characters involved.
V1: The dawning revolution
Keywords: Biographies; Brouwer L E J; Mathematicians